PROFIL GENERASI Y : STUDY OF VALUES (SOV) PADA MAHASISWA DI YOGYAKARTA - Mulyati, Rina; Gusniarti, Uly (Nathiqiyyah, 2022)
The period of the 2000s in university are dominated by college students from Generation Y or also known as the Millennium/Millennial. They born when the innovation of modern science and technology have growth rapidly. This research aims to find the dominant values of students from generation Y in Yogyakarta and to confirm the differences between types of values at state and private universities students. The instrument that used to detect the type of student’s value was SoV (Study of Values) that developed by Allport, Vernon and Lindzey. There are six types of measured values, i.e. theoretical, economic, aesthetic, social, political, and religious. Subjects in this study were students from State Universities and Private Universities that derived from various faculties and departments. State Universities were represented by the two universities (90 students) and Private Universities represented by three universities (135 students). The results of the analysis using Independent Sample T Test showed that there was no difference in the type of the students value in state and private universities. The higher classification based on mean score of students’ value were social and economic types. While the type of theoretical, aesthetic, religious, and political values have mean scores in the medium category.